Detection of ions in water using electrostatic induction - Lim, Charmaine Jia Min (Nanyang Technological University, 2021)
Triboelectricity has been a field of energy generation that has been widely studied. Triboelectric nanogenerators (TENG) is a device that is self-powered and a very feasible solution to convert the mechanical energy into electrical energy. Due to it being versatile, it can also be applicable in many areas of human activities and specifically satisfying the increasing demand of internet of things (IoT). In this project, we made use of contact electrification (CE) between liquid–solid and electrostatic induction to harvest energy from falling water droplets. Two systems with different liquid-solid interactions were designed. The first system consisted of a copper mesh, where the water droplets passed through, and a wire on fabric as the charge collection electrode. Various solutions with different concentrations and pH values were tested, the height of water droplets’ fall was also changed. Up to 4.0μC of charge was generated by a single droplet of tap water fell from 30cm height with -0.5V and +0.5V bias on Cu mesh. The second system consisted of ITO/glass substrates with variable polymers such as Kapton and CF4/O2 RIE treatment on Kapton were coated on the surface. Both were used as the collecting electrode in the second system. With uncharged water droplets falling from a height of 30cm, up to 42nC in magnitude was generated with single droplet of uncharged tap water. The charge might be enhanced by the degree of hydrophilicity of the electrode.